On the Role of the Institute of Headmen of Academic Groups in Russian Universities - Yu. S. Ezrokh (Высшее образование в России)
The institute of headmen of academic groups is an auxiliary tool for improving the educational process in higher education. This tool is traditional for Russian Universities, but it practically is not used abroad. Based on empirical data, the article highlights its current state, formulates key problems and justifies measures to overcome them.The goal is the formation of a set of sound scientific and practical measures to improve the educational process in Russian higher education by developing the institute of headmen of academic groups.Methodology and methods. On the basis of the questionnaire developed by the author, a student survey was conducted to explore how the institute of headmen of academic groups is functioning in one of the Russian economic universities. The total number of students who were invited to participate in the survey was 238 people (12 academic groups); the actual number of respondents was 193 (81% of students). The questionnaire was anonymous, remote, electronic, free of charge.The results and scientific novelty. The author has formulated a number of key problems characterizing functioning of the institute of headmen of academic groups at the present stage: a) the lack of proper interaction between deans and headmen; b) the lack of real authority among the headmen; c) the lack of candidates for the role of headmen; d) the lack of systems in domestic universities for: d1) attracting students with high organizational skills and leadership to perform the functions of headmen; d2) the formation of a personnel reserve of headmen; d3) supporting headmen’s activities including the development of their personal and business qualities. To overcome them, a number of recommendations have been proposed: a) to formalize the status of the institute of headmen of academic groups as an auxiliary tool for improving the educational process in order to specify the conceptual task of its functioning; b) to intensify the interaction between the organizational and educational units of deans headmen of academic groups; c) to empower councils of headmen so that they can take part in consideration of certain issues related to the implementation of the educational process; d) to create a working system for the selection, preparation and support of the activities of headmen of academic groups; e) to increase the motivation of headmen.Practical relevance. The given recommendations can be used in Russia and abroad at the state and local levels in order to improve the quality of the educational process in higher education institutions.